2007
DOI: 10.1107/s1600536807061557
|View full text |Cite
|
Sign up to set email alerts
|

N-(4-Methylphenyl)benzamide

Abstract: The structure of the title compound, C14H13NO, resembles those of N-(2-chloro­phen­yl)benzamide, 2-chloro-N-phenyl­benzamide, N-(2,3-dichloro­phen­yl)benzamide, N-(3,4-dichloro­phen­yl)benzamide and 2-chloro-N-(2-chloro­phen­yl)benzamide with similar bond parameters. The benzene and methylphenyl rings have a dihedral angle of 63.41 (5)°, while the amide group makes a dihedral angle of 20.5 (1)° with the benzene ring. The mol­ecules are linked into chains in the b-axis direction by N—H⋯O hydrogen bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
(8 reference statements)
4
6
0
Order By: Relevance
“…The N-H and C=O bonds in the amide group of (I) are trans to each other ( Fig. 1), similar to what is observed in N-(4-methylphenyl)benzamide (N4MPBA) (Gowda et al, 2008c), 2-methyl-N-(phenyl)-benzamide (NP2MBA) (Gowda et al, 2008a), and 2methyl-N-(3-methylphenyl)-benzamide (N3MP2MBA) (Gowda et al, 2008b). Further, the conformation of the amide oxygen in (I) is syn to the ortho-methyl group in the benzoyl ring, similar to what is observed in NP2MBA and N3MP2MBA (Gowda et al, 2008a, b).…”
Section: Methodssupporting
confidence: 72%
“…The N-H and C=O bonds in the amide group of (I) are trans to each other ( Fig. 1), similar to what is observed in N-(4-methylphenyl)benzamide (N4MPBA) (Gowda et al, 2008c), 2-methyl-N-(phenyl)-benzamide (NP2MBA) (Gowda et al, 2008a), and 2methyl-N-(3-methylphenyl)-benzamide (N3MP2MBA) (Gowda et al, 2008b). Further, the conformation of the amide oxygen in (I) is syn to the ortho-methyl group in the benzoyl ring, similar to what is observed in NP2MBA and N3MP2MBA (Gowda et al, 2008a, b).…”
Section: Methodssupporting
confidence: 72%
“…The structure of N4CPBA ( Fig.1) is similar to those of N-(phenyl)benzamide, N-(2-chlorophenyl)benzamide, N-(3chlorophenyl)benzamide and N-(4-methylphenyl)benzamide and other benzanilides (Gowda et al, 2003(Gowda et al, , 2007(Gowda et al, , 2008.…”
Section: S1 Commentmentioning
confidence: 66%
“…In the present work, the structure of N-(4-chlorophenyl)benzamide (N4CPBA) has been determined to study the effect of substituents on the structures of benzanilides (Gowda et al, 2003(Gowda et al, , 2007(Gowda et al, , 2008.…”
Section: S1 Commentmentioning
confidence: 99%
“…In these fluorobenzanilides, alteration of the packing modes is observed as the F-atom position changes through para to meta to ortho. In related work, Gowda et al (2008) have also reported a series of similar substituted alkyl-and chlorophenylbenzamides. Wardell et al (2008) have also recently reported an extensive series of N-arylpyrazinecarboxamides; however, the authors state that isomeric compounds in this series 'show little resemblance in the supramolecular behaviour beyond crystallization in the same space group'.…”
Section: Figurementioning
confidence: 98%
“…Usually benzamides form intermolecular N-HÁ Á ÁO C interactions [with a C(4) graph set] as their primary interaction in the absence of other competing strong donors/ acceptors (Gowda et al, 2008). In (I)-(III), the amide NH group and pyridine N-atom acceptor form amide-pyridine N-HÁ Á ÁN chains [graph set C(6)] as the primary interaction, thus preventing the formation of standard C(4) chains.…”
Section: Figurementioning
confidence: 99%